Teknik pembelajaran bahasa Inggris yang menyenangkan untuk taman kanak-kanak - Somariah Fitriani; Hamzah Puadi Ilyas (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2021)
The variety of learning by applying teaching techniques in a fun, effective and efficient manner provides an important role in the learning process of children. Therefore, this community service activity aims to train the participants' abilities in teaching techniques that are specialized in games, songs and storytelling in English. This activity was carried out by using Google Meeting for two days. In addition, the uses of learning media and class routine activities are the goal of this community service. 18 participants participated in this activity, most of whom were kindergarten teachers. The implementation was carried out using the methods of lecturing, brainstorming and discussion, demonstration and mentoring. The results show that the participants' knowledge and understanding of the given themes increased. Participants are also able to answer several questions at the end of the session and be involved in online game activities. The results of the evaluation show that this activity is very useful and beneficial in increasing their ability to implement  more varied teaching techniques that are in accordance with the abilities of kindergarten children.